PENGARUH PROMOSI, KERAGAMAN PRODUK, DAN KUALITAS PRODUK TERHADAP LOYALITAS PELANGGAN PADA CAFE FAMILY GARDEN DI KABUPATEN SITUBONDO - Yakin, Ainol; Karnadi, Karnadi; Subaida, Ida; Sari, Rini Kartika (Growth, 2022)
Organizational management requires good and appropriate management so that people who work in the organization can achieve optimal results or goals. Cafe Family Garden is a company that has duties, functions and authorities. In order to achieve the goals that have been set, it takes high loyalty from customers of Cafe Family Garden. One way to increase customer loyalty is by promotion, product diversity, and product quality. Statistical test results of the regression variable promotion (X1), product diversity (X2), and product quality (X3) have a positive influence on the customer loyalty variable (Y), this is shown in the results of multiple linear regression analysis, namely Y = -1.306E-16 + 0.163X1 + 0.348X2 + 0.453X3+ e. Partially the promotion variable (X1) tcount is 2,032 > ttable 1,985 with a sig value of 0.045 < 0.05, product diversity (X2) tcount is 3.901 > ttable 1.985 with a sig value of 0.000 <0.05, product quality (X3) tcount is 6.250 > t table 1.985 with sig value 0.000 <0.05. The promotion variable (X1) product diversity (X2) product quality (X3) has a significant positive effect on the customer loyalty variable. Simultaneously (together) promotion (X1) product diversity (X2) product quality (X3) simultaneously has a positive effect on customer loyalty variable (Y) because Fcount > Ftable, 81.729 > 2.70 with sig value 0.000 <0.05 . The dominant test of this research conducted is the influence value of the product quality variable (X3) of 6.250, which is greater than the value of the promotion variable (X1) of 2.032 and product diversity (X2) of 3.901. The coefficient of determination test (R2) obtained results of 0.723 meaning the influence of promotion variables, product diversity, and product quality had a contribution of 72.3% to the customer loyalty variable, the remaining 27.7% was influenced by other factors not included in the study.